Palladium thin films for hydrogen sensing in aqueous electrolytes. Issue 6 (24th April 2015) - Walkner, Sarah; Schimo, Gabriela; Mardare, Andrei Ionut; Hassel, Achim Walter
<x xml:space="preserve">Abstract</x> In this work, differently prepared palladium films are tested toward their hydrogen sensing properties in aqueous electrolytes. The Pd thin films were either electroless deposited, electrochemically deposited, or prepared by physical vapor deposition. The outcome of each fabrication process and characteristics of the Pd films were determined by means of SEM and cyclic voltammetry. Electrochemical impedance spectroscopy was performed in order to calibrate the prepared hydrogen sensors. The Pd films react on different hydrogen concentrations in the electrolyte by changing their electrical resistivity. Elemental hydrogen can diffuse into the Pd film leading to a lattice expansion and a phase transition. A second hydrogen sensing mechanism due to a change in charge transfer resistance can be observed.